Psychological and Subjective Well-being and Resilience of Nurses in a Level 3 Government Hospital - Landicho, Benedict; Tan, Crestita B. (MALATA SAINS INDONESIA, 2025)
Introduction: Nursing is a highly stressful profession. Filipino nurses in government hospitals experienced farther stress during the COVID-19 pandemic. However, few studies explore the impact of Psychological and Subjective Well-being to Resilience. Objectives: This study determined the significant relationship and differences of Subjective and Psychological Well-being and Resilience of Filipino nurses in terms of age, gender, work position and area of assignment. Methods: This study utilized a cross-sectional survey using 3 adopted instruments; Psychological Well-being scale by Carol Ryff, Subjective Well-being scale by Ed Diener and Brief Resilience scale by Bruce Smith. Spearman Rho Correlation with the 0.05 level of significance was used to find relationship and Mann Whitney U test was used to determine differences among the variables. Results: A total of 200 nurses responded, rendering the results of moderate level of Psychological Well-being (mean = 5.26), moderate level of Subjective Well-being (mean = 4.11) and resilience level at (mean = 3.52). PWB (r =0.253, p < 0.001) and SWB (r = 0.359, p < 0.001) had a result of weak positive and moderate positive relationship to Resilience. There was no significant difference on the variables when profile of the respondents was considered. Conclusion: Filipino nurses in government hospitals had moderate level of well-being and resilience whereas subjective well-being had stronger influence to Resilience than psychological well-being. Strategies and programs that improve well-being and resilience is beneficial to sustain a healthy workforce Filipino nurses in government hospitals.